The way to paradise - Llosa, Mario Vargas (London : Faber and Faber, 2004)
Flora died before her grandson was born, but their travels and obsessions unravel side by side in this absorbing novel.A rare study of passion, ambition and the determined pursuit of greatness in the face of illness, death and conservative forces, The Way to Paradise shows Mario Vargas Llosa at the peak of his powers.
Keywords: Painters -- Fiction. -- France; Gauguin, Paul -- Fiction